Exploring Career Selection Determinants Among Accounting Students in Indonesia: An Empirical Study Using the Theory of Planned Behavior - Dhany Efita Sari; Nadia Fauzi Asila; Suranto Suranto; Surya Jatmika; Rochman Hadi Mustofa; Siti Aisyah; Rini Agustin Eka Yanti; Erni Harlina Isdiati; Surani Dwi Astuti (AL-ISHLAH: Jurnal Pendidikan, 2025)
Occupational choice in accounting is influenced by psychological and social factors, which can be effectively analyzed using the Theory of Planned Behavior (TPB). Understanding these determinants is essential for developing strategies to attract and retain future professionals in the field. This study employed a quantitative approach to examine how TPB constructs—Attitude Toward Behavior, Subjective Norms, and Perceived Behavioral Control—influence students' intentions to pursue a career in accounting. Data were collected through a structured questionnaire administered to 134 Indonesian accounting education students. Hypotheses were tested using Structural Equation Modeling (SEM) with SmartPLS 2.3.9, chosen for its suitability in handling moderate sample sizes and complex models involving latent variables. The analysis revealed that all three TPB constructs significantly predicted students’ career choices in accounting. Attitude Toward Behavior emerged as the strongest predictor, indicating that students' positive perceptions of accounting as a rewarding and fulfilling profession strongly influence their decisions. Subjective Norms also had a significant effect, highlighting the role of social influences from family, peers, and educators. Additionally, Perceived Behavioral Control was positively associated with career intention, suggesting that confidence in personal ability and access to necessary resources supports students' career decisions. These findings suggest that accounting programs should integrate digital skills and career readiness training to align with student motivations and labor market expectations. Future research should explore additional factors to develop a more comprehensive understanding of career choice in accounting.